El juicio contencioso administrativo fiscal en México, 1853-1867 - Becerril Hernández, Carlos de Jesús (El Colegio de México, A.C., 2025)
Conceived as an administrative means of defense, Mexico’s contentious administrative appeal arose to resolve a tax issue and the nation’s revenue fell under its jurisdiction. This article analyzes its legal efficacy within the period in question, as well as the legislative and institutional context. By reviewing the cases seen by the administrative authorities, it reveals the arguments of both the authorities and the taxpayers who sought to resolve their conflicts through this legal mechanism.